Rendahnya Kemandirian Daerah Seluruh Kabupaten/Kota di Wilayah Provinsi Daerah Istimewa Yogyakarta - Muhammad Zaenuddin (EKO-REGIONAL, 2009)
The research is aimed to know the local government ability in decentralization schema according to the local government financial report that using decentralization fiscal level between central and local government. The result shows that ratio between the local government income (PAD) and total income of local government (TPD) for all local government in Yogyakarta Province in 1996-2006 is very low, less than 10%. The ratio between production sharing for tax and non-tax (BHPBP) and total income of local government (TPD) is also low. Therefore, these phenomena indicate that the ratio of decentralization financial is very low. Other ways to know the local government financial report is using independent level of government local that used the income of the local government for their budget. This shows that the local governmet income (PAD) contribution in the total expenditure of local government (TKD) is still low; therefore the local government financial autonomy is very low. According to those results, the decentralization implementation in Yogyakarta province is not success. The factors that influence in financial autonomy level are contribution level, aid level, government funding, and economy potential. These factors contribute in local government financial level at Yogyakarta Province. This paper shows that contribution level (BM) and PDRB significantly affect local government financial level. Therefore, the BM has negative relation but PDRB has positive one to the autonomy financial level. Beside that, aid variable (BN) and government funding (PP) only have a small effect in the autonomy financial level. Keywords: decentralization, financial autonomy level, local government income